Civil War and anti-Bolshevik zemstvo finances: the experience of the Perm province - V. I. Teterin (Омский научный вестник: Серия "Общество. История. Современность")
The article discusses the work of the Perm Zemstvo on solving financial, economic and economic issues traditional for local self-government during the period when the Perm province was under the rule of the government of A. V. Kolchak. The article shows how economic issues acquired special significance in the front line of the Civil War. The activities of the zemstvo in the field of tax collection, budget formation and other economic issues are analyzed. Based on unpublished sources, conclusions are drawn about the place of the financial activities of the Perm zemstvo during the establishment of anti-Bolshevik power in the province.